PENGARUH PELATIHAN CABLE CROSSOVER DAN SHOULDER PRESS TERHDAP PENINGKATAN POWER DAN KEKUATAN OTOT LENGAN - Dani Primanata; Muhammad Sidik (UNIVERSITAS PGRI ADI BUANA SURABAYA, 2023)
Aim in this study to identify: 1) the effect of cable crossover training on increasing power and arm muscle strength; (2) the effect of shoulder press training on increasing arm muscle strength and strength; 3) a comparison of the effect between cable crossover training and training shoulder press to increase power and arm muscle strength. There were 39 samples in this study and divided into 3 groups, each group consisting of 13 samples. The type of research used in this research is quantitative with quasi- experimental procedures. The research design uses a randomized control group pretest- posttest design, and data analysis uses ANOVA. The process of obtaining power information was carried out by testing throwing a medicine ball and arm muscle strength using an expanding dynamometer test during the pretest and posttest. Furthermore, information on research results was analyzed using the SPSS boost series 16.0. The conclusion of this study is that the cable crossover and shoulder press training programs have a significant effect on increasing power and arm muscle strength. Shoulder press training is more efficient than cable crossover and the control group for increasing power and arm muscle strength.